Music, nature and divine knowledge in England, 1650-1750 : between the rational and the mystical. - Dixon, Tom (Music in society and culture., 2023)
During a period of tumultuous change in English political, religious and cultural life, music signified the unspeakable presence of the divine in the world for many.